2020
DOI: 10.1002/ptr.6806
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evidence of Yinchenhao decoction on cholestasis: A systematic review and meta‐analysisof animal studies

Abstract: Cholestasis is an important cause of liver fibrosis and cirrhosis. Yinchenhao decoction has been used as a well‐known traditional Chinese medicine used in the treatment of cholestasis for over 2,000 years. The purpose of this systematic review is to evaluate the preclinical evidence of Yinchenhao decoction on cholestasis models. The following databases were searched from inception to February 2020. Chinese National Knowledge Infrastructure, VIP medicine information system, Wanfang Database, PubMed, Web of Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…The emergence of heterogeneity not only deepens the content of this review but also leaves wider issues to be explored. The occurrence of heterogeneity is influenced by multi-factors, including experimental design, study subjects, intervention measures, and results combination ( Thompson et al, 1997 ; Hooijmans et al, 2014 ; Shi et al, 2021 ). The great heterogeneity difference in this review may be due to BBR and animal diets coming from different laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of heterogeneity not only deepens the content of this review but also leaves wider issues to be explored. The occurrence of heterogeneity is influenced by multi-factors, including experimental design, study subjects, intervention measures, and results combination ( Thompson et al, 1997 ; Hooijmans et al, 2014 ; Shi et al, 2021 ). The great heterogeneity difference in this review may be due to BBR and animal diets coming from different laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it makes great sense for searching additive for liver health of fish fed on high‐carbohydrate diet. It was widely reported YCHD promoted lipids metabolism in human and mice (Shi et al, 2021). However, the beneficial effects of YCHD on fish lipids metabolism are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used to treat hepatic metabolism disease for more than 1800 years and has long been a very popular recipe in China and Japan (Li et al, 2017). Recent studies clearly indicated that YCHD has responsible therapeutic effects for non‐alcoholic fatty liver disease (NAFLD), significantly down‐regulate hepatic total cholesterol (TC) and triglyceride (TG), and non‐esterified fatty acid (NEFA) content (Shi et al, 2021). The active ingredients of YCHD have been identified, such as chlorogenic acid, geniposide, quercetin, anthraquinones, catechin and so on (Cho et al, 2010; Huang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional Chinese medicine (TCM) is widely applied in various chronic diseases due to its low price and fewer side effects (Ahmed et al, 2020; Shi et al, 2021). Recently, more and more attentions have been paid to the clinical application and experimental study of TCM for DR treatment (Ai et al, 2020; Ou, Yang, & Peng, 2019).…”
Section: Introductionmentioning
confidence: 99%